2019
DOI: 10.1039/c8nr10357g
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic channels from bio-inspired templated supramolecular assembly of J-aggregate nanowires

Abstract: High quality J-aggregate nanowires obtained from complexation of dendronized polymers with J-aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[ 21 ] Therefore, improving the PLQY by reducing the non‐radiative decay channels of J‐aggregates is necessary to enhance the performance of the hybrid systems discussed above. [ 19,20,22–25 ] Furthermore, emitters with ultra‐narrow PL spectra are of great importance in active pixel display technologies, where the narrow‐emission band could result in emitting devices with more brilliant colors. However, the low PLQY typical for regular J‐aggregates hampered their wide‐spread use in such devices, an opportunity that could come within reach once the PLQY is boosted to the level of common‐used organic emitting compounds, with PLQY above 50%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Therefore, improving the PLQY by reducing the non‐radiative decay channels of J‐aggregates is necessary to enhance the performance of the hybrid systems discussed above. [ 19,20,22–25 ] Furthermore, emitters with ultra‐narrow PL spectra are of great importance in active pixel display technologies, where the narrow‐emission band could result in emitting devices with more brilliant colors. However, the low PLQY typical for regular J‐aggregates hampered their wide‐spread use in such devices, an opportunity that could come within reach once the PLQY is boosted to the level of common‐used organic emitting compounds, with PLQY above 50%.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have observed such changes when depositing J-aggregates on functionalized surfaces. 38 Here we found, however, that J-aggregate films retained the desired optical properties such as high oscillator strength and narrow absorption width (Fig. 1d).…”
Section: Molecular and Solvent Engineering Approach For J-aggregate Tmentioning
confidence: 58%
“…49 In previous work, we showed that Jaggregate formation can also be induced in acetate buffer even at low dye 10 concentration. 38,50 We applied the same strategy successfully to the J780 and J980 dyes and obtained narrow-banded aggregates in solution. Compared to the monomer absorption obtained from methanol solution, the absorption peaks are redshifted by 100-200 nm and present significantly narrowed widths ( Fig.…”
Section: Molecular and Solvent Engineering Approach For J-aggregate Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoactive molecules, including J-aggregates, have undergone a renaissance due to their important roles in light-harvesting materials such as the ones found in photovoltaic cells and nonlinear optical devices. They are also used in numerous areas of applied research such as molecular electronics, nonlinear optics, waveguides, photodetection, , molecular plasmonics, and artificial photosynthesis. …”
Section: Introductionmentioning
confidence: 99%